Хронология “срсднеаварского” периода - Гавритухин, И.О. (Степи Европы в эпоху средневековья, 2001)
The paper beargs on chronological scheme of the mid-Avarian period and develops further the authors’s views in terms of update investigations and publications. Attention is drawn to the importance of these materials for better understanding Eastern European antiquities. The author does not consider the attempts of some researchers to differentiate in their periodisation schemes the time when an artifact was manufactured and the time it got into a settlement layer or in a grave, to be of much relevance. In fact, such “periods” cover the time from a certain set of goods or their typical trait formation up to the time it becomes replaced by another set.